The Influence of Company Size, Leverage, and Ownership Concentration on Audit Report Lag - Nurul Pratiwi; Mazda Eko Sri Tjahjono; Tri Wahyudi (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
This study aims to analyze the effect of company size, leverage, and ownership concentration on audit report lag. The research objects used in this study are Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This study employs a quantitative approach with secondary data sources consisting of audited annual financial statements and annual reports obtained through the official website (www.idx.co.id). The research sample was selected using a purposive sampling method, resulting in 305 observational data  from 61 companies. The analytical technique employed was panel data regression analysis using EViews 12. The results show that company size and ownership concentration have a negative and significant effect on audit report lag. These findings indicate that large-scale companies possess operational advantages, and majority shareholders with high ownership concentration exert substantial control over the company, thereby enabling faster completion of the audit report lag. However, leverage does not have a significant effect on audit report lag. This result suggests that the level of corporate debt does not influence the length of the audit report lag, as auditors work in accordance with applicable professional standards